The Foreign Exchange Reserve and Economic Crisis: Evidence from Bangladesh - Saifullah, Mohammad; Huq, Md. Mahmudul; Akhter, Mst. Momena (Asian Business Review, 2025)
The paper attempts to reveal different aspects of Bangladesh’s ongoing foreign exchange reserve crisis. Data from the Bangladesh Bank shows why Forex reserves have recently decreased. Deferring payment during COVID, higher cost of imports, lower export revenue, and the devaluation of the Taka are a few of the factors. In the short term, the Government has acted exactly as it should have - capping the fancy tours, pampering the remitters, creating entry barriers for luxury products, scaling up exports, and attracting FDI. Its medium-term action includes bringing back illicit money that crossed borders to raise reserves. This study focuses on those aspects that are yet to be done. Production should be increased, and imports should be reduced further. Money laundering must be dealt with firmly. Increasing market supervision and keeping products reasonable are also essential for economic stability. Employment should be created through small industries; easy loans should be disbursed to promote self-employment. Significant sectors cannot be allowed to go bankrupt, and developing alternative export markets is also essential. Last but not least, it emphasizes supervising the actions of government employees at all levels to eliminate corruption.